KEMAMPUAN INFORMASI LABA DAN ARUS KAS DALAM MEMPREDIKSI ARUS KAS MASA DEPAN - Widyawati, Zuli; Sukartha, I Made (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This study aimed to obtain empirical evidence about ability information of earning and cash flows in predicting future cash flows year 2012, 2013 and 2014. Prediktors of earning and cash flows will be compare to determine the better predictorin predicting future cash flows. The population is taken from entities listedin in Indonesia Stock Exchange period 2002-2014. Analysis technique used is simple linier regression. The testing result shows that earning and cash flows has the ability to predicting future cash flows. The different test in absolute term, shows that cash flows is better than earning in predicting future cash flows. While the testing result in stastically shows that there no differences between predictors of earning and cash flows in predicting future cash flows.
Keywords: Earning, Operating Cash Flow, Prediction, MAPE